Characterization of internal flow and spray of multihole di gasoline spray using X-ray imaging and CFD - Lai, Ming Chia; Zheng, Yi; Shost, Mark; Xie, Xingbin; Matsumoto, Atsushi; Wang, Jin; Zhang, Xusheng; Moon, Seoksu; Gao, Jian; Fezzaa, Kamel; Zigan, Lars; Schmitz, Ingo; et al. (SAE Technical Papers, 2011)
Multi-hole DI injectors are being adopted in the advanced downsized DISI ICE powertrain in the automotive industry worldwide because of their robustness and cost-performance. Although their injector design and spray resembles those of DI diesel injectors, there are many basic but distinct differences due to different injection pressure and fuel properties, the sac design, lower L/D aspect ratios in the nozzle hole, closer spray-to-spray angle and hense interactions. This paper used Phase-Contrast X ray techniques to visualize the spray near a 3-hole DI gasoline research model injector exit and compared to the visible light visualization and the internal flow predictions using with multi-dimensional multi-phase CFD simulations. The results show that strong interactions of the vortex strings, cavitation, and turbulence in and near the nozzles make the multi-phase turbulent flow very complicated and dominate the near nozzle breakup mechanisms quite unlike those of diesel injections. © Copyright 2011 Society of Automotive Engineers of Japan, Inc. and SAE International.
Created from Fastlane, Scopus look-up

Charakterisierung von Benzindirekteinspritzprozessen mit analytischen und numerischen Modellen basierend auf optischer Spraydiagnostik - Zigan, Lars; Dias Flügel, Alexandre; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (Thermodynamik-Kolloquium und Ingenieurdaten, 2009)

Effect of fuel properties on primary breakup and spray formation studied on a gasoline 3-hole nozzle - Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred; et al. (23rd Annual Conference on Liquid Atomization and Spray Systems, 2010)
The initial conditions of spray atomization and mixture formation are significantly determined by the turbulent nozzle flow. In this study the effect of fuel properties on primary breakup and macroscopic spray formation was investigated with laser based measurement techniques at a 3-hole research injector in an injection chamber. Two single-component fuels (n-hexane, n-decane), which are representative for high- and low-volatile fractions of gasoline with sufficient large differences in viscosity, surface tension and volatility were studied. Integral and planar Mie-scattering techniques were applied to visualize the macroscopic spray structures. To characterize the microscopic spray structure close to the nozzle exit a high resolving long distance microscope was used. For deeper insight into primary breakup processes with effects on global spray propagation the range of Reynolds (8,500-39,600) and liquid Weber numbers (15,300-44,500) was expanded by variation of the fuel temperature (25 °C, 70 °C) and injection pressure (50 bar, 100 bar). The spray is characterized by strong shot-to-shot fluctuations and flipping jets due to the highly turbulent cavitating nozzle flow. Significant differences in microscopic spray behavior were detected at valve opening and closing conditions, whereas during the quasi-stationary main injection phase the spray parameters cone angle and radial spray width show a plateau-trend for the different fuels. The radial spray width at the nozzle exit as well as the microscopic cone angle decrease by trend with higher Reynolds and Weber numbers at early injection phases leading to increased macroscopic spray propagation. The fine scale analysis showed chaotic structure of the disintegrating jet at the beginning injection phase with intense ligament formation depending on fuel properties and the turbulent cavitating nozzle flow. <br

Effect of fuel properties on spray breakup and evaporation studied for a multihole direct injection spark ignition injector - Zigan, Lars; Schmitz, Ingo; Flügel, Alexandre; Knorsch, Tobias; Wensing, Michael; Leipertz, Alfred (Energy & Fuels, 2010)
Mixture formation in spray-guided direct injection spark ignition engines (SG-DISI) with late injection timing is mainly controlled by spray atomization and evaporation and strongly depends on fuel properties. The influence of fuel composition on the liquid spray structure was determined for a 12-hole solenoid injector with integral and light sheet Mie scattering as well as phase Doppler anemometry (PDA). Late injection timing in a high pressure atmosphere was simulated in an injection chamber (1.5 MPa, 293 and 673 K) to characterize the spray propagation and evaporation of alkanes with high and low volatility (n-hexane, n-heptane, n-decane) and a 3-component mixture of these alkanes with similar fuel properties like gasoline fuel. Under high chamber pressure and low ambient temperature, the spray propagation and the resulting droplet sizes are similar for all fuels. However, for n-decane, the droplet size distribution is shifted to smaller droplets and the spray appeared to be less dense because of fuel-dependent internal nozzle flow which results in a reduced injected fuel mass. In contrast, under high ambient temperature conditions for more volatile fuel components, the liquid spray length is reduced and droplet size as well as droplet momenta are decreased. Small amounts of high boiling fractions delay the evaporation and support the overall spray stability also for multicomponent mixtures which is indicated by increased spray length as well as larger droplet sizes and momenta. Moreover, the droplet size distributions and the small liquid Peclet numbers (PeL ≈ 1) of the 3-component fuel indicate a demixing of light and heavy boiling components in the 3-component fuel under conditions which are typical for DISI strategies with late injection. © 2010 American Chemical Society.
Created from Fastlane, Scopus look-up

Einfluss der Kraftstoffeigenschaften auf die Sprayausbreitung und -verdampfung bei Piezo-Einspritzventilen - Zigan, Lars; Dias Flügel, Alexandre; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (Motorische Verbrennung Aktuelle Probleme und moderne Lösungsansätze (IX. Tagung), 2009)

Entwicklung eines analytischen Spraymodells für Direkteinspritzung - Dias Flügel, Alexandre; Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred; Lutz, Michael (Motorische Verbrennung Aktuelle Probleme und moderne Lösungsansätze (IX. Tagung), 2009)

Experimentelle und numerische Untersuchung zum Einfluss der Kraftstoffeigenschaften auf die Düseninnenströmung und den Strahlaufbruch bei der Benzindirekteinspritzung - Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (Motorische Verbrennung – aktuelle Probleme und moderne Lösungsansätze, 2011)

Influence of fuel properties on spray formation and evaporation - Zigan, Lars; Schmitz, Ingo; Dias Flügel, Alexandre; Wensing, Michael; Leipertz, Alfred; et al. (Indo-German Seminar on Future Mobility, 2010)

Influence of the fuel properties on spray formation and evaporation measured on a piezoelectric injector for 2nd generation gasoline direct injection - Zigan, Lars; Schmitz, Ingo; Dias Flügel, Alexandre; Wensing, Michael; Leipertz, Alfred (Conference Injection Systems for IC Engines, 2009)

Investigation of fuel effects on spray atomization and evaporation studied for a multi-hole DISI injector with a late injection timing - Zigan, Lars; Ammon, Markus; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred; Gupta, Vivek (SAE International Journal of Fuels and Lubricants, 2012)
The influence of fuel composition on sprays was studied in an injection chamber at DISI conditions with late injection timing. Fuels with high, mid and low volatility (n-hexane, n-heptane, n-decane) and a 3-component mixture with similar fuel properties like gasoline were investigated. The injection conditions were chosen to model suppressed or rapid evaporation. Mie scattering imaging and phase Doppler anemometry were used to investigate the liquid spray structure. A spray model was set up applying the CFD-Code OpenFOAM. The atomization was found to be different for n-decane that showed a smaller average droplet size due to viscosity dependence of injected mass. And for evaporating conditions, a stratification of the vapor components in the 3-component fuel spray was observed. © 2011 Society of Automotive Engineers of Japan, Inc.
Created from Fastlane, Scopus look-up

Investigation of significant Spray Rotation Phenomena under Flash-Boiling Conditions studied on a Multi-hole DISI-Injector for Bio-Ethanol E85 and Gasoline E5 - Heldmann, Markus; Knorsch, Tobias; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (23ND ANNUAL CONFERENCE ON LIQUID ATOMIZATION AND SPRAY SYSTEMS, 2011)

Modell zur Berechnung der Eindringtiefe unter Berücksichtigung der Kraftstoffverdampfung, Motorische Verbrennung - Dias Flügel, Alexandre; Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred; et al. (Motorische Verbrennung – aktuelle Probleme und moderne Lösungsansätze, 2011)

Reynolds number effects on atomization and cyclic spray fluctuations under gasoline direct injection conditions - Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (Fuel Systems for IC Engines, 2012)

Semi-Empirical Model to Calculate Spray Length Considering Evaporation Effect - Dias Flügel, Alexandre; Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (23rd Annual Conference on Liquid Atomization and Spray Systems, 2010)
In order to improve air/fuel mixture, fulfilling the European Emission Standard and to reduce fuel consumption, injection and combustion systems have to be improved. The understanding of spray formation and evaporation has been the great challenge of last years in modern gasoline direct-injection (GDI) and Diesel engine as well as aerospace technology. For engine development, the most essential spray data are the cone angle, axial and radial penetration under various injection conditions. The purpose of this work is developing a semi-empiric spray model which is able to predict a single jet penetration of a plain orifice injector, typically from a Diesel or GDI atomizer by different temperatures and pressures based on dimensional analysis theorem. Equations were found to prognosticate the spray penetration and an exponent factor which is able to correct the evaporation effect. The results are satisfactory and the improvement of calculation is possible by adding phenomena such as drag force and air entrainment.<br

Structure of evaporating single- and multicomponent fuel sprays for 2nd generation gasoline direct injection - Zigan, Lars; Schmitz, Ingo; Flügel, Alexandre; Wensing, Michael; Leipertz, Alfred (Fuel, 2011)
In the present paper the effect of fuel properties on spray formation and evaporation was investigated for a hollow-cone spray of a piezoelectric injector for Direct Injection Spark Ignition (DISI) engines. Late injection timing in a high-pressure atmosphere (1.5 MPa, 200 °C) was simulated in an injection chamber. Liquid and vapor phase structure of the hollow-cone spray were studied with 2D-Mie scattering, laser-induced fluorescence (LIF) as well as phase-Doppler anemometry (PDA). The spray structure was investigated for several alkanes with high and low volatility (n-hexane, n-heptane, iso-octane, n-decane) and a three-component mixture of the n-alkanes with similar fuel properties like a multicomponent gasoline fuel. It is found that the rapid evaporation of high volatility fuels can lead to spray destabilization, whereas low volatility single-component fuels overestimate radial spray propagation and vortex formation. For iso-octane the droplet size distribution is shifted to smaller droplets and the spray appeared to be less dense compared to n-heptane despite almost identical boiling behavior. However, the much higher viscosity of iso-octane determines the internal nozzle flow which results in a reduced injected fuel mass and changed atomization. A well defined three-component fuel models the global spray characteristics as well as the droplet size, droplet momentum distribution and evaporation behavior of the used multicomponent gasoline fuel very precisely. Small amounts of low volatility fractions delay the droplet evaporation and support the overall spray stability also for multicomponent mixtures. This leads to an increased spray width as well as larger droplet sizes and momenta. The evaporation characteristic of multicomponent fuels at increased ambient pressure is complex. At the studied injection conditions it is situated between the two limiting cases of distillation-like behavior and coevaporation of the components. Moreover, the results in comparison with theoretical estimations indicate a demixing of light and heavy boiling fractions in the three-component and multicomponent fuel under conditions which are typical for DISI strategies with late injection. © 2010 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Atomization; Evaporation; Gasoline direct injection; Multicomponent fuels; Spray structure

Structure of evaporating single- and multi-component fuel sprays for DISI-engines - Zigan, Lars; Schmitz, Ingo; Dias Flügel, Alexandre; Wensing, Michael; Leipertz, Alfred; et al. (33rd International Symposium on Combustion, 2010)

Structure of evaporating single and multi component fuel sprays for gasoline direct injection - Zigan, Lars; Schmitz, Ingo; Flügel, Alexandre; Wensing, Michael; et al. (Gordon Research Conference, 2009)